2019
DOI: 10.3389/fmicb.2019.01219
|View full text |Cite
|
Sign up to set email alerts
|

A Haloarchaeal Small Regulatory RNA (sRNA) Is Essential for Rapid Adaptation to Phosphate Starvation Conditions

Abstract: The haloarchaeon Haloferax volcanii contains nearly 2800 small non-coding RNAs (sRNAs). One intergenic sRNA, sRNA132, was chosen for a detailed characterization. A deletion mutant had a growth defect and thus underscored the importance of sRNA132. A microarray analysis identified the transcript of an operon for a phosphate-specific ABC transporter as a putative target of sRNA132. Both the sRNA132 and the operon transcript accumulated under low phosphate concentrations, indicating a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 55 publications
(82 reference statements)
2
15
0
1
Order By: Relevance
“…Northern blot analyses were essentially performed as described [59]. In short, H. volcanii cultures were grown in complex medium to mid-exponential growth phase.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…Northern blot analyses were essentially performed as described [59]. In short, H. volcanii cultures were grown in complex medium to mid-exponential growth phase.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…IntaRNA prediction reveals that the 3’ end of the s479 interacts with the coding region of znu C1. The energy gain predicted for the interaction implies a stable sRNA-target pairing (Kliemt et al, 2019). The few examples of archaeal sRNA-target pairs described to date suggest a non-universal mode of action and a wide variability in the site of target contact (Buddeweg et al, 2018b; Gomes-Filho et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that intergenic sRNAs of H. volcanii are differentially expressed in response to growth phase or environmental stimuli including temperature, salinity, as well as oxidative stress (Straub et al, 2009; Babski et al, 2011; Fischer et al, 2011; Gelsinger and DiRuggiero, 2018a). Their profound biological role is unquestioned as growth phenotypes have been demonstrated for sRNA deletion mutants in response to temperature, salt, alternative carbon-sources, phosphate availability and oxidative stress (Straub et al, 2009; Fischer et al, 2011; Heyer et al, 2012; Jaschinski et al, 2014; Kliemt et al, 2019). Besides growth, swarming behaviour or cell shape have been affected by sRNA deletions as well (Jaschinski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, hundreds of differentially expressed ncRNAs in response to oxidative stress were identified in H. volcanii [22]. In H. volcanii, sRNA132 is important for rapid adaptation to phosphate starvation [23]. Recently, Tsai et al [24] identified 41 ncRNA candidates in D. radiodurans by the genome-wide RNA sequencing approach but the functional roles of these ncRNAs are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%